Rehabilitating gullies with low cost methods, in the sub humid Ethiopian highlands - Addisie, Meseret B.; Ayele, Getaneh K.; Gessesse, A.A.; Tilahun, Seifu A.; Moges, M. M.; Zegeye, Assefa D.; Mekuria, Wolde; Schmitter, Petra S.; Langendoen, E.J.; Steenhuis, Tammo S. (2016)
Gully erosion in the highlands of Ethiopia has reduced agricultural productivity and degraded ecosystem services. To better understand the processes controlling gully erosion and design effective control measures, a study was conducted in the headwaters of the Birr watershed for three consecutive years (2013-2015). Fourteen gullies with similar morphology were studied in three adjacent sub-watersheds. Stabilization measures were applied to 5 of the 14 gully heads. Three gully control measures were compared: a) reshaping gully banks and head to a 45 degree slope with stone rip rap on the gully heads, b) controlling gully bed grade, and c) planting grasses and trees on shallow gullies (i.e., < 3 m deep). Results demonstrated that gully control measures were effective in controlling the expansion of gullies as no further retreat was observed for the 5 treated gully heads, whereas the average retreat was 3 meters with a maximum of 22.5 m for the 9 untreated gullies. The migration of untreated gully heads produced an average soil loss of 38 tons per gully. Compared with simple reshaping of gully heads, the additional integration with stone rip rap was an effective and low cost measure. Vegetative treatment by itself could not stop the upslope migration of gully heads, though it had the potential to trap sediments. Re-vegetation at gully heads stabilized with stone rip rap occurred faster than at unprotected, reshaped heads and banks. From the fourteen rehabilitation treatments, gully head protection integrated with plantation showed the largest potential in decreasing gully development in terms of labor, time and material it requires.